Histamine neurons in the tuberomamillary nucleus: a whole center or distinct subpopulations? - Blandina, Patrizio; Provensi, Gustavo; Munari, Leonardo; Passani, Maria Beatrice (Frontiers in Systems Neuroscience, 2012)
Histamine axons originate from a single source, the tuberomamillary nucleus of the posterior hypothalamus, to innervate almost all CNS regions. This feature, a compact cell group with widely distributed fibers, resembles that of other amines systems, such as noradrenaline or serotonin, and is consistent with a function for histamine over a host of physiological processes, including the regulation of the sleep-wake cycle, appetite, endocrine homeostasis, body temperature, pain perception, learning, memory and emotion. An important question is whether these diverse physiological roles are served by different histamine neuronal subpopulation. While the histamine system is generally regarded as one single functional unit that provides histamine throughout the brain, evidence is beginning to accumulate in favour of heterogeneity of the histamine neurons. The aim of this review is to summarize experimental evidence demonstrating that histamine neurons are heterogeneous, organized into functionally distinct circuits, impinging on different brain regions, and displaying selective control mechanisms. This could imply independent functions of subsets of histamine neurons according to their respective origin and terminal projections.